Alternative funding sources for University of the Philippines Diliman Libraries - Coballes, Brian Aljer B.; Lapuz, Elvira B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Academic libraries face economic crisis. High cost of maintenance and other operating expenses and the great need to modernize libraries challenge head librarians of the academic libraries of the University of the Philippines, Diliman Campus.
The study used the twenty-six college or unit libraries of the U.P. Diliman Survey questionnaires were given to the head librarians of there libraries regarding the issue of alternative funding sources and other related matter. Descriptive statistics was utilized to analyze the data. The study found out that the major source of funding the University of the Philippines, Diliman Libraries is from the budget allocation of the U.P. Main Library depending on the number of enrollment each semester. Majority of the head librarians responded that their library needs alternative funding mainly from their alumni. Other feasible funding sources can come from fund granting foundations to which their college is related, from library fees, and from gifts and donations from donors. Few of the libraries do not need another alternative funding at this point because they are well supported by their college and other foundation. It is recommended that head librarians conduct seminars regarding fund raising for academic libraries. They can also start to tap their alumni for further support and think of other creative ways of generating funds.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) Library -- Finance